Effectiveness of the Volunteer Teaching From Home Program in Welcoming Education in the Era 5.0 - Antin Rista Yuliani; Wulandari, Catur (Early Publishing, 2024)
Education in the current era is often referred to as modern education. This means that education cannot be separated from the role of information and communication technology. Meanwhile, if you look at the current situation and conditions of Indonesia, it is being attacked by an epidemic which is affecting several aspects of life. One of them is in the educational aspect. The presence of this epidemic seems to give us